PENGARUH MOTIVASI, PERSEPSI DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN JARINGAN INTERNET PADA PT TELEKOMUNIKASI INDONESIA DI KOTA BATAM - Nora Pitri Nainggolan; Muhammad Anano (JURNAL AKUNTANSI BARELANG, 2019)
In the current era of globalization, business development has been characterized by various kinds of competition in all fields of business. Seeing these needs causes entrepreneurs to increasingly demand the right strategy to meet sales targets. This study aims to discuss partially, Motivation towards internet network purchasing decisions at PT Telekomunikasi Indonesia, and discuss partially. PT Telekomunikasi Indonesia, discussed some of the consumer attitudes towards internet network purchasing decisions at PT Telekomunikasi Indonesia and assessed simultaneously motivational motivation, perceptions and attitudes of consumers towards internet network purchasing decisions at PT Telekomunikasi Indonesia. The method used in this study is a linear multiple regression analysis method. The research design used was descriptive analysis. The test consists of validity test, reliability test, classic assumption test, multiple regression analysis, coefficient of determination, t-test and f-test. The population in this study were consumers of PT Telekomunikasi Indonesia with a total sample of 384 people. By using the SPSS version 21 software program. The conclusion is the partial variable motivation, Perception and Attitude of Customers has a significant effect on Purchasing Decisions, simultaneously the variables of motivation, perception and attitudes of consumers have a significant effect on internet network purchasing decisions at PT Telekomunikasi Indonesia